PERANCANGAN SISTEM INFORMASI ABSENSI SISWA BERBASIS WEB PADA SMK N 42 JAKARTA MENGGUNAKAN METODE EXTREME PROGRAMMING - Adeka Saputra; Ade Rosadi; Fadhil Is Hakim; Saprudin (Journal of Research and Publication Innovation, 2023)
Attendance is part of an institution's reporting activities, containing attendance data that is managed to find out the number of attendance at an event so that related parties can find and use easily whenever they need it. At SMK N 42 Jakarta, the attendance system is still carried out manually, starting from recording attendance data to making reports which often cause errors so that making reports becomes inaccurate. Another problem, which occurs a lot in document storage such as frequent loss of data or archives. The purpose of this practical work is to design information systems to solve these problems. The creation of this attendance system uses data collection methods from SMK N 42 Jakarta, field supervisor interviews, literature studies that support problem solving and Unified Modelling Language (UML) for software design and software testing using the Extreme Programming (XP) method. The results and benefits of this design are to provide facilities for teachers to make attendance to students so that the processing of attendance data becomes more structured and reduces the risk of student attendance data errors. In addition, students can also check attendance that has been inputted by the teacher.